2011
DOI: 10.1136/jclinpath-2011-200274
|View full text |Cite
|
Sign up to set email alerts
|

A clinicopathological aspect of primary small-cell carcinoma of the uterine cervix: a single-centre study of 25 cases

Abstract: The higher proportion of positive labelling of Syn, CD56, CgA, and NSE in SCCC implicated that they are valuably applied in a differential diagnosis of the malignancy. The patients with SCCC receive one to three types of therapies, including surgery, chemotherapy and radiotherapy, and have a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…However, past studies have shown disagreement in the 5-year overall survival (OS) rate of SCNEC. The lowest rate was reported by Li et al as 4% [3] and the highest was reported by Chen et al as 51% [4].…”
Section: Introductionmentioning
confidence: 79%
“…However, past studies have shown disagreement in the 5-year overall survival (OS) rate of SCNEC. The lowest rate was reported by Li et al as 4% [3] and the highest was reported by Chen et al as 51% [4].…”
Section: Introductionmentioning
confidence: 79%
“…Attention to the histologic features of neuroendocrine differentiation and the immunohistochemical staining of neuroendocrine markers is necessary to reach a correct diagnosis. CD56 is known to be a less specific neuroendocrine marker compared to chromogranin and synaptophysin [ 11 , 20 , 55 ]. The common coexistence of NEC and epithelial tumors along with the monoclonality of the two components implies a common cellular origin of the neuroendocrine and epithelial components [ 17 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chromogranin, synaptophysin, and CD56 are commonly used neuroendocrine markers. However, CD56 is considered a less specific marker of neuroendocrine differentiation compared to chromogranin and synaptophysin [ 11 , 20 ]. This staining should be carefully interpreted, as CD56 can be present in non-NECs, such as squamous cell carcinomas and adenocarcinomas [ 20 ].…”
Section: Neuroendocrine Tumors Of the Uterine Cervixmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of SCCC was aided by immunohistochemical staining for common neuroendocrine markers, including Syn, CgA, neuron-specific enolase (NSE) and CD56. Typically, SCCC samples exhibit 100, 96.0, 68.0, 76.0, 40.0, 84.0, 68.0 and 8.0% positivity for NSE, Syn, CD56, CgA, thyroid transcription factor-1, epithelial membrane antigen, cytokeratin and S100 immunohistochemical biomarkers, respectively ( 5 ).…”
Section: Discussionmentioning
confidence: 99%